Benefits, drawbacks, and future trends of Brayton helium gas turbine cycles for gas-cooled fast reactor and very-high temperature reactor Generation IV nuclear power plants - Gad-Briggs, Arnold; Osigwe, Emmanuel O.; Pilidis, Pericles; Nikolaidis, Theoklis; Sampath, Suresh; Teixeira, Joao Amaral (American Society of Mechanical Engineers (ASME), 2020)
Numerous studies are on-going on to understand the performance of generation IV (Gen IV) nuclear power plants (NPPs). The objective is to determine optimum operating conditions for efficiency and economic reasons in line with the goals of Gen IV. For Gen IV concepts such as the gas-cooled fast reactors (GFRs) and very-high temperature reactors (VHTRs), the choice of cycle configuration is influenced by component choices, the component configuration and the choice of coolant. The purpose of this paper to present and review current cycles being considered—the simple cycle recuperated (SCR) and the intercooled cycle recuperated (ICR). For both cycles, helium is considered as the coolant in a closed Brayton gas turbine configuration. Comparisons are made for design point (DP) and off-design point (ODP) analyses to emphasize the pros and cons of each cycle. This paper also discusses potential future trends, include higher reactor core outlet temperatures (COT) in excess of 1000 °C and the simplified cycle configurations.